Approval rating and opinion of outpatients and general practitioners toward generic drugs: a questionnaire-based real-world study - Mattioli F; Siri G; Castelli F; Puntoni M; Zuccoli ML; Stimamiglio A; Martelli A (Patient Preference and Adherence, 2017)
F Mattioli,1 G Siri,2 F Castelli,1 M Puntoni,2 ML Zuccoli,1 A Stimamiglio,3 A Martelli1 1Department of Internal Medicine, Clinical Pharmacology and Toxicology Unit, University of Genoa, 2Clinical Trial Unit, Scientific Directorate, E.O. Galliera, Genoa, 3General Practitioner, Italian National Health System, Local Health Authority: ASL3 Genovese, Genoa, Italy Purpose: Generic drugs use in the Liguria region is higher than the Italian average, but lower than in other European countries. No data exist about real-life prescription and level of awareness of generic drugs. In this study, we analyzed demographic, social, economic and cultural factors that may affect the level of awareness of generic drugs and their effective use.Methods: We conducted a population survey using a structured questionnaire, administered to a sample of 8 outpatient clinics of general practitioners located in different districts of Genoa (Liguria, Italy). Multivariate logistic modeling was adopted to study the relationship between awareness/use of generic drugs and characteristics of subjects.Results: Out of 2,000 outpatients surveyed, 95% were aware of generic drugs: these were mostly females (OR =2.2, 95% CI: 1.4–3.6), >35 years old (OR >6.0 vs 18–35 years), with a high level of education (OR >4.4 vs “elementary sch”), living in the west side of the city (OR =1.9 vs center); of these, only 59% declared that they effectively use generic drugs. Users were younger (OR =3.1, 18–35 years vs >65 years), with a high level of education (high school/university degree vs no title/elementary/secondary school OR =1.7), and were aware of the lower cost compared with branded drugs, and were mainly informed by pharmacists and physicians.Conclusions: Although subjects were substantially aware of the existence of generic drugs, ~40% still did not use them; doubts about their efficacy seem to be mainly driven by the idea that cheaper drugs lead to lower product quality, in terms of efficacy, safety and tolerability. New education policies on generic drugs are needed. Keywords: generic drug, population-based survey, generic substitution, opinion, experience